Fragments of prochymosin produced in Escherichia coli form insoluble inclusion bodies. - McCaman, M T (1989)
Bovine prochymosin produced in Escherichia coli has been used as a model system to investigate factors which may cause a recombinant protein to accumulate as insoluble inclusion bodies. A series of plasmids was constructed to investigate the effect of deletions within the prochymosin-coding sequence on protein inclusion body formation. The results demonstrated that as much as 70% of the prochymosin-coding sequence could be deleted with no significant reduction in the accumulation of insoluble protein. The smallest deletion product identified (11,000 molecular weight) retained only one cysteine, yet this product still accumulated as an insoluble product in E. coli.